2012
DOI: 10.1021/bi201676y
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Bound Water Molecules in Primate Red- and Green-Sensitive Visual Pigments

Abstract: Protein-bound water molecules play crucial roles in the structure and function of proteins. The functional role of water molecules has been discussed for rhodopsin, the light sensor for twilight vision, on the basis of X-ray crystallography, Fourier transform infrared (FTIR) spectroscopy, and a radiolytic labeling method, but nothing is known about the protein-bound waters in our color visual pigments. Here we apply low-temperature FTIR spectroscopy to monkey red (MR)- and green (MG)-sensitive color pigments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 42 publications
4
50
1
Order By: Relevance
“…Wat2a involves three hydrogen bonds to Ser186, Cys187, and Glu181, and Wat2b is located near Glu113 and stabilizes the protonated Schiff base of the retinal chromophore 34 . Alternatively, a previous analysis of the water signals for MG and MR indicated that the negative dipole moment of the oxygen side of the water molecule, which was possibly localized at the β-ionone ring side of retinal for MR, would associate with a spectral red-shift in absorbance 15 . The identification of MB water signals using site-directed mutational studies provides several insights into the mechanism of the spectral blue-shift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wat2a involves three hydrogen bonds to Ser186, Cys187, and Glu181, and Wat2b is located near Glu113 and stabilizes the protonated Schiff base of the retinal chromophore 34 . Alternatively, a previous analysis of the water signals for MG and MR indicated that the negative dipole moment of the oxygen side of the water molecule, which was possibly localized at the β-ionone ring side of retinal for MR, would associate with a spectral red-shift in absorbance 15 . The identification of MB water signals using site-directed mutational studies provides several insights into the mechanism of the spectral blue-shift.…”
Section: Resultsmentioning
confidence: 99%
“…This vector was expressed in the HEK293T cell line and regenerated with 11- cis -retinal 14, 15 . The regenerated sample was solubilized with a buffer that contained 2% (w/v) n-dodecyl-β-D-maltoside (DDM), 50 mM HEPES, 140 mM NaCl, and 3 mM MgCl 2 (pH 6.5) and purified by adsorption on an antibody-conjugated column.…”
Section: Methodsmentioning
confidence: 99%
“…This could be one of the reasons for the presence of several internal water molecules in M/LWS pigments. 26 Residue W265 in helix VI is highly conserved in all the three pigments and continues to remain in van der Waals contact with the β-ionone ring of retinal. 13 …”
Section: Resultsmentioning
confidence: 99%
“…By using the highly accurate Fourier transform infrared (FTIR) spectra, proteinbound water molecules in the red and green cone pigments have been identifi ed (Katayama et al 2012 ). The water signals were found to differ not only from those of rhodopsin but also between the red and green cone pigments ( Fig.…”
Section: Animal (Type-2) Rhodopsinsmentioning
confidence: 99%
“…Light-minus-dark difference Fourier transform infrared (FTIR) spectra of monkey red ( a ), monkey green ( b ), bovine Rh ( c )(Katayama et al 2012 ), and squid Rh ( d )(Ota et al 2006 ), with 11cis -retinyl, in the 2,750-1,800 cm −1 region measured at 77 K. Red and blue lines represent the spectra in D 2 O and D 2 18 O, respectively, and green labeled frequencies correspond to those identifi ed as water-stretching vibrations. Light-minus-dark difference Fourier transform infrared (FTIR) spectra of monkey red ( a ), monkey green ( b ), bovine Rh ( c )(Katayama et al 2012 ), and squid Rh ( d )(Ota et al 2006 ), with 11cis -retinyl, in the 2,750-1,800 cm −1 region measured at 77 K. Red and blue lines represent the spectra in D 2 O and D 2 18 O, respectively, and green labeled frequencies correspond to those identifi ed as water-stretching vibrations.…”
mentioning
confidence: 99%